Environmental Rehabilitation in Waste Management Disposable House-hold Medical Mask - Maria Novita Apriyani; Aldira Mara Ditta Caesar Purwanto; Tio Naulita Aritonang (Future Science, 2022)
Environmental health has the aim of realizing a healthy environmental quality, both physical, chemical, biological, and social that allows everyone to achieve the highest degree of health. The problem of increasing waste has become a major issue in addition to the large number of Indonesian people who have been exposed to COVID-19. Masks are the biggest source of waste today, proper mask waste management will certainly have a good impact on the environment. Disposable medical mask waste in the community is generally thrown away without any effort to separate household waste and medical waste to the Final Disposal Site (TPA). Disposable medical mask waste management, especially in the community, requires environmental rehabilitation for a sustainable and environmentally friendly living environment. Based on these facts, it is necessary to conduct a study on how to regulate Covid-19 medical mask waste, especially those produced by households, and be studied from the perspective of the environmental health law. The research method used is included in the realm of non-doctrinal legal research because the object studied in addition to the law in a normative concept is also the law in an empirical concept. The approach chosen in this study is empirical juridical. The results of this study indicate that B3 waste management, especially disposable medical masks in providing environmental health protection can be carried out in the form of medical waste management, especially B3 types with gravity flow type Autoclave procedures, increasing public awareness to separate or destroy medical mask waste, Accelerate the availability of facilities Medical waste management throughout Indonesia and Issuing Regional Regulations related to Covid-19 medical waste disposal regulations.